Predictors of Mortality in Patients with Penetrating Inferior Vena Cava Injuries Surviving to the Operating Room. Issue 10 (October 2015) - Maciel, James D.; Plurad, David; Gifford, Edward; DeVirgilio, Christian; Koopmann, Matt; Neville, Angela; Putnam, Brant; Kim, Dennis Y.
Inferior vena cava (IVC) injuries are associated with significant morbidity and mortality. To identify clinical factors associated with mortality in patients undergoing operative intervention for penetrating IVC injuries, a retrospective review of 98 patients was performed, excluding blunt injuries (n = 20) and deaths before surgery (n = 16). The overall mortality was 58 per cent. Nonsurvivors more commonly presented with hypotension (50% vs 23%, P = 0.03) and underwent resuscitative thoracotomy more frequently (42% vs 4%, P = 0.01). Retrohepatic injuries were more common among nonsurvivors ( P = 0.04). There was no difference in the use of ligation (7% vs 17%, P = 0.29) or the massive transfusion protocol (35% vs 25%, P = 0.41). On multivariate analysis, after controlling for mechanism of injury, admission hypotension, Glasgow Coma Scale score, preoperative cumulative fluids, resuscitative thoracotomy, absence of spontaneous tamponade, and location of IVC injury, the only independent predictor of mortality was the absence of spontaneous tamponade at the time of laparotomy (odds ratio = 5.4, 95% confidence interval: 1.11–25.95; P = 0.04). Penetrating IVC injuries continue to be associated with a high mortality, particularly among patients with free intraabdominal hemorrhage at laparotomy. Large multicenter studies are required to define the optimal resuscitative and operative management techniques in these severely injured patients.